Rasio-Rasio Keuangan Di PT. Bank Bukopin - Alvida Risma Safitri; Darwin Erhandy (Indonesian Journal of Economics Application (IJEA), 2019)
The purpose of this study is to analyze whether the Financial Ratios (BOPO, CAR AND NPL) effect on ROA at PT. Bank Bukopin in the period 2012-2016. The data examined in this study is secondary data, compiled from audited financial statements. In this study, data was interpolated from year to quarter, so the number in this study was 20 data. Data analysis techniques in this study using multiple linear regression analysis. The results show, every 1% increase in the BOPO ratio will increase ROA by 0.024%; 1% increase in the CAR ratio will increase ROA by 0.012%; every 1% increase in the NPL ratio will increase ROA by 0.872%. The adjusted R Square value is 63.70%, the remaining 36.30% is influenced by other factors outside of this model.